The Character of the Wayfarer in Gyula Krúdy’s Novel The Travelling Companion - Balogh, Gyula (Ethnographica et Folkloristica Carpathica, 2025)
In Gyula Krúdy’s texts, the author’s alter ego figures and mediator types can be given a new meaning with the help of the results of folklore research. The writer got to know the archetypal features of these figures very early on, as even when reading the writings of his youth, it is striking that Krúdy not only wrote the plot and atmosphere of the mostly family-based fairy tales and ghost stories into his texts, but also used the storytelling techniques that create the folklore treasure. The study will discuss Krúdy’s short novel The Travelling Companion, the division of the main character’s identity, the wide range of reading possibilities offered by the story’s sacred character and mystical atmosphere. The present interpretation undertakes to reveal the complex personality of the travelling companion, to examine those scenes abounding in sacred elements, through a detailed analysis of which the common features of the Krúdy hero and certain figures of the folk religious world become visible. It can be assumed that Krúdy knew and used in his works certain features of the accompanying, helping spirit, the so-called soul guide, psychopompos, which term denotes Hermes, the god of travel. However, the term psychopompos is not only known in cultures based on Greek myths, it also applies to the accompanying spirits of ancient shamanism. We find the remains of this belief in shamans in the case of the so-called wayfarers, who, together with other strange people, are considered late descendants of shamans.